Efeitos cardiovasculares do composto [RU(BPY)2(Tioureia)(NO)](FOR 0812) em ratos normotensos e hipertensos - Cabral, Pedro Henrique Bezerra (2016)
Ruthenium coordinated nitric oxide donors which do not release cyanide can be less toxic models for the development of drugs to treat angina and hypertensive crisis. The compound [Ru(bpy)2(tioureia)NO(PF6)3]– FOR0812, was synthesized and probed in vitro for its potential vasodilator activity and in vivo for its antihypertensive properties. First, we tested its effects on thoracic aortic rings harvested from male Wistar rats (200-250g). The rings were mounted in 5 ml organ baths in Krebs-Henseleit warmed to 37°C and gassed with 5%CO2 in 95%O2. The tissues were coupled to isometric force transducers under a 1g passive tension and coupled to a data acquisition system and recorded by using LabChart 7.0. FOR0812 was added cummulatively (10-12 a 10-4M) in aortic rings precontracted with phenylephrine or high potassium (60mM). On the other hand, in order to test the potential antihypertensive effects of FOR0812 the drug was administred at 1mg/kg by the oral route during 15 days to 2kidney-1clip hypertensive rats (2K-1C), Dahl salt-sentitive rats (DS) and to spontaneously hypertensive rats (SHR). In addition, the acute effects of intravenous bolus injections of 0.001- 1mg/Kg FOR0812 on systemic hemodynamics and cardiac eletromechanics were also studied by using microtip pressure-volume catheters inserted in the left ventricle and electrocardiogram analysis.FOR 0812 induced a concentration-dependent relaxation of 103±2.3 % with an IC50 of 0.24 µM[0.084 – 0.72] while the positive control sodium nitroprusside had a maximal relaxant effect of 108±5.3% with an IC50 of 0.05 µM[0.025 –0.12]. 100 µM L-NAME did not affect the maximal vasorelaxation induced by FOR0812 but reduced potency by 8-fold. Nevertheless, the vasorelaxant effect of FOR0812 was completely blunted by ODQ (10µM), (*p<0.05). The potency for the vasorelaxant of FOR0812 was reduced 5.8-fold by glibenclamide, 5.4-fold by apamin-carybdotoxin and by 11-fold by tetraethylammonium. The vasorelaxant response was greatly blunted by a nitric oxide scavenger, hydroxocobalamin (FOR0812=103±2.3 % vs. FOR0812+hydroxocobalamin=32.4%, *p<0.05). However, the removal of nitroxyl anions (NO-) with 3 mM L-cystein, did not affect the vasorelaxant effect of FOR0812. Similarly, the blockade of RhoA/Rho kinase (ROCK) with fasudil (HA-1077) did not affect the vasorelaxant effect of FOR0812. The blockade of prostaglandin synthesis with indomethacin did not affect the maximal vasorelaxation incuced by FOR0812 but reduced its potency by 2-fold. Strikingly, FOR0812 reduced mean arterial blood pressure (MAP) of 2K-1C rats from 181.5±3.6 mmHg to 149±3.1 mmHg after 4 days of treatment and continued to decrease MAP towards normal levels and at the end of the experimental period, i.e., 15th day the MAP of control rats was 171.1±3,2 mmHg while rats treated with FOR0812 had values of 111.4±6.9 mmHg. In the group treated only with vehicle (saline) the MAP continued high during the whole experimental period (>160mmHg). FOR also reduced MAP of DS rats from 158.8± 5.6 mmHg to 122.6±6.7mmHg after six days of treatment and this effect lasted throughout the experiment and at the end the control group treated with vehicle had MAP of 158.9±4.2 mmHg while DS rats treated with FOR0812 had MAP of 118.1±5.8mmHg. The intravenous injection of FOR at 0.001; 0.01; 0.1 and 1 mg/Kg decreased vascular resistance (expressed in mmHg x ml/min) of normotensive rats from control values of 6.5±0.8 to 5.6±0.7;4.9±0.6; 4.8±0.6 and 2.6±0.6, respectively. FOR0812 increases in a dose-dependent fashion the systolic work and cardiac output due to decreased afterload. At the higher doses, this compound decreases cardiac maximal dP/dt due to decreased left ventricular pressure. However, at the dose range used, the preload recruitable stroke work is not affected. In conclusion, FOR0812 has antihypertensive effect decreasing cardiac afterload and can decrease wall stress and myocardial oxygen demand in patients with hypertension and acute ischemic heart disease.